Invasive Pulmonary Aspergillosis after COVID-19 Pneumonia - David, Filipa; Rodrigues Morais, Joana; Beires, Francisca; Greefield, Helena; Fernandes, Gonçalo L (European Journal of Case Reports in Internal Medicine, 2022)
COVID-19 emerged in China in late 2019 and quickly spread worldwide. The severe immunomodulation and depletion of lymphocytes caused by the virus and its therapy led to an increase in the incidence of superinfections. COVID-19-associated pulmonary aspergillosis (CAPA) is a new entity with increasing incidence and high associated mortality. We present the case of a 68-year-old patient admitted to our ward after recovering from severe COVID-19 pneumonia. Due to worsening of her clinical condition, chest computed tomography was performed and a lung abscess was documented with the identification of Aspergillus niger. Despite therapy with voriconazole, the patient’s condition deteriorated, culminating in her death. COVID-19 emerged in China in late 2019 and quickly spread worldwide. The severe immunomodulation and depletion of lymphocytes caused by the virus and its therapy led to an increase in the incidence of superinfections. COVID-19-associated pulmonary aspergillosis (CAPA) is a new entity with increasing incidence and high associated mortality. We present the case of a 68-year-old patient admitted to our ward after recovering from severe COVID-19 pneumonia. Due to worsening of her clinical condition, chest computed tomography was performed and a lung abscess was documented with the identification of Aspergillus niger. Despite therapy with voriconazole, the patient’s condition deteriorated, culminating in her death.